Upholding the Right to Healthy Environment through Judicial Interpretation of the Right to Life - Abdulkadir Bolaji Abdulkadir (Pancasila and Law Review, 2023)
The late twentieth century has experienced an unprecedented increase in legal claims for human rights and the environment. The correlation between the two subjects became apparent following the Stockholm Conference of 1972. The Stockholm Conference laid the foundation for the interconnectedness between protecting the environment and realizing the protected human rights in national and international human rights instruments. This is because it has since become obvious that environmental pollution can infringe on protected rights such as the right to life, the right to peaceful enjoyment of property, and the right to privacy, to mention but a view. Therefore, any attempt to ensure the protection of the environment will invariable and enhances the realization of basic human rights.Consequently, human rights have become a legal weapon in a claim to environmental protection through judicial interpretation and expansion of the existing human rights provisions in national and international human rights instruments. Although various fundamental rights have been interpreted to encompass the protection of the environment, this paper is limited in its scope to the concept of the right to life. Examining the two most important questions has been the purpose of discussion throughout this paper. First is the degree of willingness of the Court to adopt an extensive interpretation of the right to life to protect the environment. The other is whether the courts expand traditional human rights principles. In answering these questions, this paper looks into the courts' approach through case law for proper evaluation of the right to life in protecting the environment. Likewise, the paper adopts a doctrinal legal research method. The doctrinal legal method is issues-based and involves analysis of laws and conceptual clarifications of fundamental issues depending on the objective and purpose of a research work. Therefore, within the objective of this paper, the doctrinal research method is employed in analyzing the right to a healthy environment and the judicial approach to using the right to life in preventing environmental pollution and enhancing a healthy environment.